PLATIDIA ANOMIOIDES (SCACCHI & PHILIPPI) E PLATIDIA DAVIDSONI (DESLONGCHAMPS) (TEREBRATULIDA, BRACHIOPODA) NEL PLEISTOCENE DELLA SICILIA ORIENTALE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The present paper deals wirh a Platidia (Brachiopoda, Terebratulida)faunule, collected in the lower Pleistocene of SE Sicily, Italy. Two species, P. anomioides (Scacchi & Philippi, 1844) and P. davidsoni (Deslongchamps, 1855) are recognized. The southernmost part of Italy is the only one area, where these species are so far recognized as fossil. Presently, they are largely spread in Mediterranean and Atlantic, living from the circalittoral to the bathyal stages. From the morphological point of view, is here confirmed the absence of complete descending branch connecting the crura to the septum in P. davidsoni. The shell microstructural study has been carried our both on fossil and recent specimens. P. davidsoni has a thick secondary layer with sinuous fibers, resulting in an apparent scattered fiber orientation. P. anomioides instead, has few thick fibers in the secondary, sometimes not fully welded together. No relevant differences occur between fossil and recent specimens.
Keywords: Brachiopoda; Platidia; Taxonomy; Morphology; Pleistocene; Sicily.